Genotypic differences in growth and ions accumulation in soybean under NaCL salinity and water stress conditions - Khan, MSA; Karim, MA; Haque, MM (Bangladesh Agronomy Journal, 2015)
Salt and water stress tolerance of the seven soybean genotypes viz. BARI Soybean 6, BD 2329, BD 2342, AGS 95, BGH 02026, Galarsum and BD 2331 were evaluated for their performance at 0 and 100 mM NaCl under well watered & water stress (watering with 70% depletion of available water at wilting) conditions at the Banghabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur. The results indicated that all the growth parameters like plant height, shoot dry weight, root dry weight and dry matter distribution in different plant parts of the genotypes sharply decreased when the plants were exposed to water stress, salt stress and, combined salt and water stress conditions. Among the genotypes reduction in dry matter production was the least in Galarsum and BD 2331 in both the salt stress and, the combined salt and water stress conditions. These genotypes also accumulated lower amount of Na+ and higher amount of K+ in leaf tissues under salt stress and, combined salt and water stress environments as compared to others. Bangladesh Agron. J. 2014, 17(1): 47-58